Elections in the Public Sphere: the Analysis of Lithuanian TV Debates „Lyderių Forumas“ - Valiauskaitė, Aistė (Žurnalistikos tyrimai, 2011)
The article analyses the information that spreads in the media during the election campaign. It looks at the aspect of promises made by politicians through an academic lens. The definition of a political promise is explained; some insights are devoted to an analysis of the reasons why some promises are more commonly fulfilled. The paper mostly concentrates on the role of the media, combining ideas of media theorists with the investigation of pre-election TV debates “Lyderių forumas”. Keywords: campaign, objectivity, parliamentary elections, political communication, professionalism, promise, tv debates.